SECONDARY SCHOOL STUDENT' ATTITUDE TOWARDS THE VALUES OF PHYSICAL EDUCATION - Vidran Kljajević (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
Investigation is attended on 320 students who are members of third class of Secondary school. They are divided into three groups-two experimental groups and one control group. The first experimental group E1 had its own curriculum with basketball contents. The second experimental group had this programme too, but with motorics elements which are added in basketball section. Control group K had 'standard' curriculum with contents of athletics, gymnastics and basketball. During this investigation we used system of pedagogical experiment with parallel groups. These programmes made changes which are supervised in three directions-morphological, biomotorical and psycho-social. The aim of this part of research was to see if there is any significiant difference in contribution of the realization of the programs in educational process during this research on forming the positive attitudes of the students from the groups E1, E2 and C.